Metal ion-enhanced photosynthetic bacteria for bioplastic production from kitchen waste digestate: performance and mechanism - Zhao, Wei; Liu, Huize; Li, Jingyi; Liu, Shiqi; Tao, Xue; Sun, Li; Lv, Longyi; Liang, Jinsong; Zhang, Guangming (Frontiers in Microbiology, 2025)
BackgroundPolyhydroxybutyrate (PHB) production from food waste by photosynthetic bacteria (PSB) face the bottleneck of low production efficiency. Metal ions have the potential to enhance the PHB production by PSB. Thus, for the first time, this study explored the effect of Fe3+ and Mn2+ on the enhancement of PHB production from kitchen waste digestate by PSB and their enhancement mechanism.MethodsFeCl3·6H2O and MnCl2·4H2O were the main sources of Fe3+ and Mn2+. Five Hundred milliliter sealed Schott bottles were used as the fermentation reactor. Kitchen waste digestate was diluted to soluble chemical oxygen demand (SCOD) of 2.5 g/L as substrate and inoculated with 20% (v/v) mixed PSB. Fe3+ concentrations in these reactors were 10, 20, 30, and 40 mg/L, respectively. Mn2+ concentrations in these reactors were 1, 2, 3, and 4 mg/L, respectively. The initial pH of these reactors was adjusted to 8.0 and was carried out at room temperature of 26–30°C. All reactors were placed in a light-proof experimental chamber with a light intensity of 4,000 lx.ResultsThe optimal concentrations of 10 mg/L Fe3+ and 2 mg/L Mn2+ promoted PSB biomass and PHB accumulation, while excessive concentrations of metal ions inhibited them. Concentrations of PSB biomass reached 2366.3 and 2109.2 mg/L, respectively under the 10 mg/L Fe3+ and 2 mg/L Mn2+ concentrations, and PHB content reached 46.0 and 43.8%, respectively. Removal rate of SCOD and ammonia nitrogen in the kitchen waste digestate exceeded 90 and 70% under the 10 mg/L Fe3+ and 2 mg/L Mn2+ concentrations. The concentration of intracellular Fe3+ and Mn2+ that PSB adapts to growth was approximately 5.5 and 0.5 mg/L, respectively. The 10 mg/L Fe3+ and 2 mg/L Mn2+ concentrations decreased the diversity, altered the composition, and enhanced functional metabolism of microbial communities.ConclusionThe concentration of 10 mg/L Fe3+ and 2 mg/L Mn2+ significantly enhanced PSB biomass and PHB accumulation (p < 0.05). Enhancement mechanism was to increase the relative abundance of key microorganisms, improve metabolic functions, and promote the expression of key functional genes. This study provides new ideas and insights for efficient production of PHB.